KEPATUHAN PERAWAT MELAKSANAKAN STANDAR OPERASIONAL PROSEDUR PENCEGAHAN RISIKO JATUH DALAM UPAYA PENCEGAHAN RISIKO JATUH DI RUMAH SAKIT: LITERATUR REVIEW - Shinta Nurwantika; Ahmad Hamkani (CV. Adiba Aisha Amira, 2025)
Background: Patient Safety in Hospitals (PSH) is a system designed to ensure patient safety during the provision of healthcare services. This system encompasses six safety objectives, one of which remains a serious concern: patient falls, particularly among inpatients. The objective of this study is to analyse nurses' compliance with Standard Operating Procedures (SOPs) for fall risk prevention in relation to fall risk prevention efforts in hospitals. This research used a literature review design, searching for literature in three databases, namely Google Scholar, Pubmed, and Sciencedirect, using the keywords ‘nurse compliance,’ ‘standard operating procedures,’ and ‘fall risk.’ The articles used in this literature review were published in the last five years, from 2020 to 2025. Based on the screening results, 10 articles were found to meet the criteria relevant to the research question. The findings of several studies revealed that nurse compliance is influenced by various internal and external factors that are interrelated. Knowledge level, age, and workload significantly influence nurse compliance in implementing fall risk prevention SOPs. Nurses with good knowledge and controlled workloads tend to be more compliant in performing procedures. The conclusion of this study is that nurses' compliance in implementing SOPs for fall risk prevention is the result of a complex interaction between knowledge, attitude, work experience, caring, motivation, and organisational and facility support. Although SOPs are available, their implementation is often not optimal due to various structural and personal barriers.